Guidelines for Higher Education Libraries in Portugal - Sanches, Tatiana; Costa, Maria Teresa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This study reports the recent activity of the Higher Education Libraries Work Group, a group of the Portuguese Association of Librarians, Archivists and Documentation Professionals. It focuses particularly on the reflection and debate about the production of the Guidelines for Higher Education Libraries that are published here. The study analyses some of the best practices held in higher education libraries that inspired the construction of this document and that can be observed to raise awareness to the most needed areas of intervention. It also aims to reach out to the strategic objectives of generating knowledge, sharing experiences, promoting the transfer of knowledge and fostering the creation of policies in the field of information and documentation in Portugal.